Breastfeeding and Postpartum Amenorrhea in Rural Guatemala - Pinto Aguirre, Guido; Jones, Robert E. (Población y Salud en Mesoamérica)
The association between breastfeeding patterns and resumption of postpartum menstruation was examined in rural Guatemalan women from the INCAP longitudinal study (1969-1977). It was distinguished among women who experienced infant mortality before menses resumed, women who weaned before menses resumed, and women who had return of menses while still breastfeeding. Weaning and infant mortality before menses resumes are significant risk factors for resumption of postpartum menstruation. Among those women whose menses resumed while still nursing or who remained amenorrheic and nursing at lose to follow-up or the end of the study, low number of nursing bouts per 24-hr day and the early introduction of supplements to the child were significant risk factors for the return of postpartum menstruation.